Difficult knots of the bioethics today. - Serra, Angelo (Medicina e Morale, 2003)
The last fifty years of the century XX has seen an exponential progress in the field of the sciences of life. Some big benefits for the humanity followed and will follow. At the same time, science and technology imposed procedures and activities that injure human dignity and rights under the pressure of a culture dominated by an ideological and ethical pluralism, that has darkened clear certainties on essential human values. Between these particularly: the production of embryos "in vitro" to reproductive purposes or tool of search; the suppression of embryos and foetuses carriers of actual or potential serious diseases, and attempts for the amelioration of the human kind. The contrast above these serious deviations, that prevail today, is strong, but it is necessary, through a suitable education on these themes, to illuminate who is seduced unconsciously by these novelties, without knowing the serious damages that they achieve for the whole society.